1984
DOI: 10.1037/0012-1649.20.6.1210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on memory for presentation modality.

Abstract: Two experiments were conducted to examine evidence for the automatic processing of information about presentation modality in older adults. Young (mean age = 22 years) and older adults (mean age = 69 years) were asked to learn a mixedmodality (auditory and visual) list of nouns, then to recall the target words, and finally to identify the presentation modality of each word on a recognition list. Half of the participants in each study were told in advance to also remember modality information. The experiments d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…As mentioned above, there is plenty of empirical support for the notion that memory tasks that involve contextual information are more responsive to inductions than memory tasks that only demand a re‐activation of already present representations (Johnson et al , 1993; Light, 1991). In particular, studies in memory and aging have shown that elders have more difficulties in remembering information of the source or attributes of the stimulus items (Erngrund et al , 1996; Kausler & Puckett, 1980; Lehman & Mellinger, 1984; Park & Puglisi, 1984).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, there is plenty of empirical support for the notion that memory tasks that involve contextual information are more responsive to inductions than memory tasks that only demand a re‐activation of already present representations (Johnson et al , 1993; Light, 1991). In particular, studies in memory and aging have shown that elders have more difficulties in remembering information of the source or attributes of the stimulus items (Erngrund et al , 1996; Kausler & Puckett, 1980; Lehman & Mellinger, 1984; Park & Puglisi, 1984).…”
Section: Methodsmentioning
confidence: 99%
“…As a support for this reasoning, several studies suggest that tasks requiring an integration of contextual information are more sensitive to experimental manipulations of episodic memory than those requiring a mere activation of pre‐existing memory representations (see Johnson, Hashtroudi & Lindsay, 1993; Light, 1991). For example, cognitive aging research shows that elderly people have more trouble than younger adults in remembering whether information was presented auditorily or visually (Lehman & Mellinger, 1984; McIntyre & Craik, 1987), in upper or lower case letters (Kausler & Puckett, 1980), or in a particular color (Park & Puglisi, 1985). Furthermore, Erngrund, Mäntylä and Nilsson (1996) reported selective age differences in source memory, so that the magnitude of age difference was greater for source recall than for item memory.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that source error occurs because of a failure to notice, integrate, or retain specific details associated with the initial event (Hashtroudi et al, 1989(Hashtroudi et al, , 1990Shimamura and Squire, 1987). There is certainly evidence indicating that older adults are less likely than younger adults to recollect the modality in which successfully recalled words were originally presented (e.g., Lehman & Mellinger, 1984;Light, La Voie, Valencia-Laver, Albertson-Owens, & Mead, 1992), they are less likely to remember the order of recalled events (Kausler & Wiley, 1990), the spatial location of otherwise successfully recalled pictures (Zelinski & Light, 1988), or the spatial location of objects that had been recalled (Puglisi, Park, Smith, & Hill, 1985).…”
Section: Behavioral Source Memory Paradigmsmentioning
confidence: 99%
“…Older adults are less able than young adults to remember the context for speci¢c events, for example, whether they read a word or generated it themselves from a cue (Rabinowitz 1989), whether a word was presented in the visual or auditory modality (Lehman & Mellinger 1984) or whether a word was thought or actually spoken (Hashtroudi et al 1989;see Spencer & Raz (1995) for a review). Older adults also make more errors than young adults in specifying the source of events: for example, older adults are more likely to erroneously remember that they had seen a sequence of actions performed when they had in fact imagined seeing them performed (Cohen & Faulkner 1989;see Johnson et al (1993) for a review).…”
Section: (A) Episodic Memorymentioning
confidence: 99%